Hole transfer dynamics from dye molecules to p-type NiO nanoparticles : effects of processing conditions - Tan, Serena L. J. (2013)
Hole transfer dynamics of Atto647N sensitized p-type NiO nanoparticle (NP) thin films is investigated using both ensemble-averaged and single-molecule spectroscopy techniques. The rate of hole transfer is dependent on the processing conditions and is enhanced when the NiO is pre-annealed in air as compared to vacuum. This is possibly due to an upward shift of the valence band of the semiconductor and an increase in the free energy for hole transfer as more Ni2O3 are formed in the presence of air. The stretched exponential fluorescence decay profile of Atto647N on NiO NP suggests the presence of a distribution of hole transfer rates. This is in agreement with the observed emission lifetime and intensity fluctuations and non-monoexponential fluorescence decays for individual Atto647N molecules on NiO NP films. A plausible explanation for the heterogeneous hole transfer rates is an inhomogeneous distribution of (defect) sites on the metal oxide due to the processing conditions and a fluctuation in the intermolecular interaction.